Secure RSSI-based node positioning mechanism for wireless sensor networks - EA-yong Y; Li XU; Hui LIN (Tongxin xuebao)
For securing the RSSI-based ranging,a new protocol was proposed firstly,which achieved robustness by applying integrity coding and occupation of communication channel.The theoretical analysis showed the proposal was resilient to most conventional attacks including signal forgery and replay,also it can prevent adversary from attenuating the ranging signal,which reducing the measured distance.Furthermore,a new secure node positioning scheme for sensor networks was proposed by applying the proposed protocol above,in which,the distance enlargement attacks were further filtered out by verifiable multilateration.The detailed analysis was also given to shown it’s robustness under external attacks.